Dampak Paparan Konten Video dengan High-Speed Transition terhadap Kemampuan Atensi dan Regulasi Emosi Anak Usia Dini - Lilis Darmila; Siti Alawiah Biastri Pelawi; Rosmidar Rosmidar; Erni Suyani (Pusdikra Publishing, 2026)
In the current digital era, early childhood is intensively exposed to short-form video content characterized by high-speed transitions. This rapid visual stimulation is strongly suspected of affecting neural development during a child's golden age. This study aims to analyze the impact of fast-paced visual stimulation on attention span and emotional regulation in early childhood through a global literature review. This research employs a library research method, analyzing various international research drafts, pediatric medical journals, and relevant cognitive psychology studies from the past decade. The synthesis of the literature indicates that rapid image transitions (scene duration <3 seconds) trigger cognitive fatigue and weaken the brain's executive functions. Children consistently exposed to fast-paced content tend to experience a decreased attention span and difficulty managing frustration (emotional regulation) due to habituation to instant gratification. Excessive visual stimulation from the formal features of modern digital media poses a risk to a child's self-control abilities. Strict parental moderation of the type of content and visual pacing of media consumed in early childhood is recommended.